Vertebrate biodiversity in King Khalid Royal Nature Reserve, Central Saudi Arabia, with a new range-expansion of Trachylepis tessellata - ABDULLAH A. ALMUTAIRI; MOHAMMED F. ALBESHR; EHAB EID (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Almutairi AA, Albeshr MF, Eid E. 2025. Vertebrate biodiversity in King Khalid Royal Nature Reserve, Central Saudi Arabia, with a new range-expansion of Trachylepis tessellata. Biodiversitas 26: 4065-4076. Arid protected areas in Central Saudi Arabia remain under-surveyed for vertebrate diversity, constraining evidence-based management. King Khalid Royal Nature Reserve (KKRNR), an arid habitat mosaic northeast of Riyadh, Saudi Arabia, lacks contemporary faunal baselines. We conducted the first systematic, year-round assessment of vertebrates in KKRNR to compile a field-verified checklist, highlight notable distributional records, and identify conservation-value habitats. In 2023, we sampled four habitat types (wadis, dunes, plains, plateaus) across 19 fixed sites using complementary methods: diurnal/nocturnal line transects, fixed-radius point counts, visual-encounter surveys, camera trapping (760 trap-days), Sherman live-trapping (665 trap-nights), and verified opportunistic records. We documented 77 species (14 mammals, 43 birds, 20 reptiles), including eight globally threatened taxa and two introduced breeding residents. Birds comprised the largest share (43/77; 56%), consistent with KKRNR’s location on the Palearctic–African flyway. Seasonal richness peaked in autumn (57 species) and was lowest in winter (28), with significant seasonal differences (ANOVA F = 12.84, p < 0.001). Spatial patterns were pronounced: wadis supported the highest diversity (Shannon H? = 2.73; evenness J? = 0.84), whereas dunes and plateaus were comparatively species-poor, underscoring moisture and structural complexity as key drivers. We confirmed a range extension of the tessellated mabuya (Trachylepis tessellata) into the Riyadh region, with seven individuals near cultivated, mesic microhabitats, suggesting broader habitat tolerance or prior under-detection. These results establish a current baseline and pinpoint wadi networks as priority habitats for protection and restoration. Management should safeguard and rehabilitate wadis, regulate grazing/infrastructure on dune and plateau margins, and institute long-term monitoring that couples standardized surveys with passive acoustics and environmental DNA to improve detection of cryptic taxa. The findings align with Saudi Arabia’s Vision 2030 objectives for effective protected-area management and biodiversity monitoring in arid ecosystems.